The Role of Ultrasound in the Diagnosis of Soft Tissue Tumors - Aparisi Gómez, Maria Pilar; Errani, Costantino; Lalam, Radhesh; Vasilevska Nikodinovska, Violeta; Fanti, Stefano; Tagliafico, Alberto Stefano; Sconfienza, Luca Maria; Bazzocchi, Alberto (Seminars in Musculoskeletal Radiology, 2020)
The vast majority of soft tissue masses are benign. Benign lesions such as superficial lipomas and ganglia are by far the most common soft tissue masses and can be readily identified and excluded on ultrasound (US). US is an ideal triaging tool for superficial soft tissue masses. Compared with magnetic resonance imaging (MRI), High-resolution US is inexpensive, readily available, well tolerated, and safe. It also allows the radiologist to interact with the patient as a clinician. In this review, we describe and illustrate the lesions with typical (diagnostic) US features. When the appearances of the lesion are not typical as expected for a benign lesion, lesions are deep or large, or malignancy is suspected clinically, MRI and biopsy are needed. The management of suspicious soft tissue tumors has to be carefully planned by a multidisciplinary team involving specialized surgeons and pathologists at a tumor center.
Keywords: soft tissue neoplasms; ultrasonography; sarcoma; lipoma; hemangioma